Flightless Phoenix: Fire Risk and Fire Insurance in Urban Canada, 1882-1886 - Norris, Darrell (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1987)
Adaptation to urban fire hazard through the medium of insurance preceded effective means of containing fire risk in Canada's cities, towns, and villages. Fire hazard was more acute in small places than large cities, yet the former were least apt to be protected by adequate insurance coverage. This paper reviews the Canadian fire insurance industry in the late nineteenth century, and considers the implications of 494 major reported fires during the 1880s. The evidence suggests that major fires in minor places contributed to their diminishing role in the commercial and industrial fabric of proto-modern Canadian urban society.